One-step nonhydrolytic sol–gel synthesis of mesoporous TiO2 phosphonate hybrid materials - Wang, Yanhui; Mutin, P. Hubert; Alauzun, Johan G. (Beilstein Journal of Nanotechnology, 2019)
Mesoporous TiO2–octylphosphonate hybrid materials were prepared in one step by a nonhydrolytic sol–gel method involving the reaction of Ti(OiPr)4, acetophenone (2 equiv) and diethyl octylphosphonate (from 0 to 0.2 equiv) at 200 °C for 12 hours, in toluene. The different samples were characterized by 31P magic angle spinning nuclear magnetic resonance, Fourier transform infrared spectroscopy, Raman spectroscopy, X-ray diffraction, and nitrogen physisorption. For P/Ti ratios up to 0.1, the hybrid materials can be described as aggregated, roughly spherical, crystalline anatase nanoparticles grafted by octylphosphonate groups via Ti–O–P bonds. The crystallite size decreases with the P/Ti ratio, leading to an increase of the specific surface area and a decrease of the pore size of the hybrid samples. For a P/Ti ratio of 0.2, the volume fraction of organic octyl groups exceeds 50%. The hybrid material becomes nonporous and can be described as amorphous TiO2 clusters modified by octylphosphonate units, where the octyl chains form an organic continuous matrix.
Keywords: anatase; mesoporous; nonaqueous sol–gel; phosphonate